Demand and Supply of Bamboo in Majuli - a Case Study - Kalita, R. R.; Chandra, A.; Mishra, H.; Zhasa, N. N. (Indian Forester, 2006)
A detailed survey on bamboo was conducted in the Majuli block of Jorhat District of Assam. Ten per cent of the total households were undertaken for the study. The average size of the family was found to be 5 and total population of the block was 1,35,378. About 68.75 % of the households had small landholding i.e. 1-2 ha. About 67.50 % of the families had kutcha types of house and remaining 32.50 % pucca types of houses. General category is the dominant caste in the area that counts 45.62 % of total population whereas SC population is least (1.88%). Mainly bamboo is used for construction and repair of house and fence, and also used as food (kharisa), firewood, etc. The total extraction and consumption of bamboo in Majuli is 84,747 and 48,736 tonnes per year. About 36,011 tonnes of bamboo is found surplus in the Majuli. The per capita extraction, consumption and surplus of bamboo is found to be 626, 360 and 266 kg per year respectively.